Influence of Bdellovibrio on Maintenance Media on The Life of Vaname Craws (Litopenaeus vannamei) Infected with Vibrio parahaemolyticus Bacteries - Farman, Yudi; Azhar, Fariq; Marzuki, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Whiteleg shrimp (Litopenaus vannamei) is one of the leading fishery commodities. Whiteleg shrimp cultivation has been widely carried out in Indonesia and has begun to cause various problems such as disease attacks. The type of disease that is often found in whiteleg shrimp cultivation is vibriosis. Vibrio parahaemolyticus bacterial infection is a type of disease that often attacks cultivated shrimp because it has the potential to cause death of up to 80%. The purpose of this study was to analyze the effect of giving Bdellovibrio flour to the maintenance media of whiteleg shrimp infected with Vibrio parahaemolyticus bacteria. This study was experimental by implementing a completely randomized design (CRD). The results of the study showed that giving Bdellovibrio at a dose of 70 ppm in water media was able to increase the immune system of whiteleg shrimp in a challenge test with Vibrio parahaemolyticus bacteria. The THC value obtained was 17.67 x 106 cells/ml, the DHC value in hyaline cells was 61%, granulocyte cells were 36%, semi-granulocyte cells were 18.67%, the AF value was 68.69%, the TBC value was 5.04 x 108 CFU/ml, the TVC value was 1.46 x 107 CFU/ml, the FCR value was 1.28 and the SR value was 77.78%.